Estimation of energy efficiency of residential buildings; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Glushkov S. V. Sergey Viktorovich; Kachalov N. A. Nikolay Aleksandrovich; Senkiv E. Elena; Glushkova V. Victoriya (2017, 2017)
Title screen